Pityriasis versicolor in children. - Ferrante, M.R. (European Journal of Pediatric Dermatology, 2006)
Pityriasis versicolor is a rare disorder in the prepubertal age. It is characterized by two peaks of increased incidence in the first year and in peripubertal age, thus starting from the age of ten in females. Its appearance is conditioned by genetic factors, more than familial contagion. The disorder in children affects most frequently the face, particularly the forehead. In 50% of cases even in children the disease runs a chronic relapsing clinical course.